School Bullying and its Relationship to the Motivation of Achievement Among a Sample of Preparatory School Students: A Field Study of Some Preparatory School in the Western Branch in Zliten - Al- Zadawi, Fatima Attia; Makhlouf, Huda Fathi (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
The aim of the research is to identify the level of school bullying and the motivation of achievement among a sample of middle school students in the Western Branch schools in the city of Zliten، and to identify the relationship between school bullying and their achievement motivation. The research also aimed to identify differences in the level of school bulling and achievement motivation according to the variables of gender and grade levels. The descriptive correlational approach was used. The research sample consisted of (76) male and female middle school students، including (45) male and (31) female students who were selected using a stratified random sampling method. The school bullying scale prepared Ali Musa Al -Subhaien (2007) was used، and the motivation scale was used. For achievement، prepared by Othman Mustafa Hazin and others (2014). The research reached the following results: that there is a negative relationship between school bullying and achievement motivation. The results also revealed that the level of school bullying and achievement motivation was high among the research sample، and that there were on statistically significant differences in school bullying. Achievement motivation according to the gender variable (males and females) and academic grades (seventh، eighth، and ninth).
Keywords: School bullying; Achievement motivation; Preparatory school students; Zliten city